2012
DOI: 10.1002/met.1346
|View full text |Cite
|
Sign up to set email alerts
|

Estimation method of grass net radiation on the determination of potential evapotranspiration

Abstract: Evapotranspiration depends primarily on the local energy balance, which is the most important variable of the physical environment when it comes to irrigation scheduling, especially throughout the production formation stages that are limited by water factors. The current manuscript will verify the applicability of estimates of grass net radiation to the performance of estimation methods of potential evapotranspiration under the climatic conditions in Piracicaba, Sao Paulo, Brazil. In order to proceed to simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…During the day, average ET D rates were mainly governed by the environmental variables R n and VPD (both very strong correlations) which agrees well with previous studies (Liu et al, ; Pereira et al, ; H. Wang et al, ). Variables like RH , T a , and T s showed a strong correlation with average ET D rates.…”
Section: Resultssupporting
confidence: 91%
“…During the day, average ET D rates were mainly governed by the environmental variables R n and VPD (both very strong correlations) which agrees well with previous studies (Liu et al, ; Pereira et al, ; H. Wang et al, ). Variables like RH , T a , and T s showed a strong correlation with average ET D rates.…”
Section: Resultssupporting
confidence: 91%
“…The choice of the ETo method is justified by its robustness and accuracy (Valiantzas, 2013). Furthermore, Pereira et al (2014) used different methods to estimate the ETc of Paspalum notatum Flügge, in Piracicaba, SP, and observed that the PM-FAO 56 method revealed the highest agreement (R 2 = 0.94) with the field measurements of ETo.…”
Section: Crop Coefficients Of Forage Cropsmentioning
confidence: 99%
“…Agric. v.76, n.6, p.448-458, November/December 2019 characteristics of this intercropping may have contributed to these values, since these grasses are small in size and covered all the soil, similar to Paspalum notatum, which is the grass used as the standard when measuring ETo (Pereira et al, 2014).…”
Section: Crop Coefficients Of Forage Cropsmentioning
confidence: 99%
“…Lysimeters are used to measure crop evapotranspiration by taking account of the crop's transpiration and soil surface evaporation. Potential evapotranspiration (Ep) is a measure of the atmosphere's ability to evaporate and transpire water from the surface [20,20,48,67,68,69]. It can be estimated via indirect methods, using empirical models such as the modified Penman Monteith FAO 56 method, Penman 1945 method, Blaney Criddle method, Hargreaves methods, Priestley-Taylor methods, and Thornthwaite method [45].…”
Section: Introductionmentioning
confidence: 99%